Comparison of 2 electrophoretic methods and a wet‐chemistry method in the analysis of canine lipoproteins. (12th January 2016) - Behling‐Kelly, Erica
Abstract : Background: The evaluation of lipoprotein metabolism in small animal medicine is hindered by the lack of a gold standard method and paucity of validation data to support the use of automated chemistry methods available in the typical veterinary clinical pathology laboratory. The physical and chemical differences between canine and human lipoproteins draw into question whether the transference of some of these human methodologies for the study of canine lipoproteins is valid. Validation of methodology must go hand in hand with exploratory studies into the diagnostic or prognostic utility of measuring specific lipoproteins in veterinary medicine. Objective: The goal of this study was to compare one commercially available wet‐chemistry method to manual and automated lipoprotein electrophoresis in the analysis of canine lipoproteins. Methods: Canine lipoproteins from 50 dogs were prospectively analyzed by 2 electrophoretic methods, one automated and one manual method, and one wet‐chemistry method. Results: Electrophoretic methods identified a higher proportion of low‐density lipoproteins than the wet‐chemistry method. Automated electrophoresis occasionally failed to identify very low‐density lipoproteins. Conclusions: Wet‐chemistry methods designed for evaluation of human lipoproteins are insensitive to canine low‐density lipoproteins and may not be applicable to the study of canine lipoproteins. Automated electrophoretic methods will likely require significant modifications if they are to be used in the analysis of canine lipoproteins. Studies aimed at determining the impact of a disease state on lipoproteins should thoroughly investigate the selected methodology prior to the onset of the study.